Transitions from Education to Work Workforce Ready Challenges in the Asia Pacific - Cameron, R.; Dhakal, Subas P.; Burgess, J. (Routledge, 2017)
This book brings together national and international perspectives on employability challenges faced by selected countries in the Asia Pacific region.